2022
DOI: 10.1186/s12877-022-03168-3
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic obesity is associated with impaired physical function and mortality in older patients with heart failure: insight from FRAGILE-HF

Abstract: Background The purpose of this study was to clarify the prevalence, association with frailty and exercise capacity, and prognostic implication of sarcopenic obesity in patients with heart failure. Methods The present study included 779 older adults hospitalized with heart failure (median age: 81 years; 57.4% men). Sarcopenia was diagnosed based on the guidelines by the Asian Working Group for Sarcopenia. Obesity was defined as the percentage of bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
0
16
0
1
Order By: Relevance
“…Sarcopenic obesity is defined as excessive fat mass accompanied by reduced muscular mass [ 24 ]. It is worth noting that this complex disorder is suggested to be associated with a higher health outcome risk than low body cell mass or high fat mass alone [ 23 , 24 , 25 ]. However, detailed body composition is needed for a full diagnosis of sarcopenic obesity [ 28 ], which is why this aspect needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcopenic obesity is defined as excessive fat mass accompanied by reduced muscular mass [ 24 ]. It is worth noting that this complex disorder is suggested to be associated with a higher health outcome risk than low body cell mass or high fat mass alone [ 23 , 24 , 25 ]. However, detailed body composition is needed for a full diagnosis of sarcopenic obesity [ 28 ], which is why this aspect needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sarcopenic obesity is another condition associated with higher mortality risk [ 23 , 24 , 25 ]. It is characterized by excessive fat mass combined with reduced muscular mass; thus, it cannot be identified by body mass measurements alone [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though different exercise orders did not affect chronic adaptations in muscle strength, hypertrophy, anabolic hormones, magnitude, and duration of postexercise hypotension in healthy older women ( 53 , 54 ), it was not possible to assume the same responses in older adults with SO. Indeed, older adults with SO potentially present impaired physical performance ( 55 ), muscle strength, and quality ( 4 ), which together can be responsible for triggering different exercise responses according to exercise order ( 56 ). Therefore, a critical evaluation of exercise order is recommended when dealing with older adults with SO, since training performance can be compromised throughout the session.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study of 11,803 older Canadian adults with SO found reduced handgrip strength but no signi cant difference in gait speed [33]. Another study of older adults with heart failure and SO found reduced physical performance, as measured by short physical performance battery score and 6-minute walk distance, and a 2.48 times higher risk of all-cause mortality compared to older adults without sarcopenia/obesity [34]. However, a study of 904 community-dwelling older adults reported no differences between the SO condition and physical performance, as measured by time up and go, sit to stand, one leg stand, walking speed at normal/fastest pace [35].…”
Section: Discussionmentioning
confidence: 99%